PDGFR-β/Cav1-induced autophagy via mTOR/FIP200/ATG13 activation in cancer-associated fibroblasts promotes the malignant progression of breast cancer - Zhang, Lifang; Wang, Keqin; Zhang, Jianbo; Qian, Xianzhe; Zhang, Xiaoan; Wang, Yi; Hu, Quan; Zhan, Ziyi; Hu, Wending; Lin, Hui; Liu, Xiaoming; Xiong, Lixia (Journal of translational medicine, 2025)
Breast cancer incidence rates have been increasing globally. Cancer-associated fibroblasts (CAFs), key stromal components of the tumor microenvironment (TME), play crucial roles in tumor growth by dynamically interacting with cancer cells. Autophagy has been extensively studied in multiple stages of the metastatic cascade. However, the roles of two key membrane proteins, platelet-derived growth factor receptor-β (PDGFR-β) and caveolin-1 (Cav-1), in regulating autophagy in CAFs and their effects on cancer cell invasion and migration remain unclear. The association between PDGFR-β expression and clinical features in breast cancer patients was analyzed using TCGA databases. PDGFR-β was either overexpressed or pharmacologically inhibited in cancer cells. Autophagy-related markers and signaling proteins were analyzed by Western blot and RT-qPCR, while lactate secretion and ROS levels were quantified. Breast cancer cell migration and invasion were evaluated through wound healing and transwell assays, and PDGFR-β/Cav1 interactions were verified by immunofluorescence and co-immunoprecipitation (Co-IP). A breast cancer mouse model was employed to assess tumor progression and autophagy modulation in vivo. The study demonstrated that PDGFR-β promotes autophagy in CAFs through the mTOR/FIP200/ATG13 signaling. PDGFR-β/Cav-1 enhanced glycolysis in CAFs via autophagy-mediated metabolic reprogramming, resulting in increased lactate export that promoted breast cancer cell growth. Furthermore, CAFs autophagy regulated breast cancer cell invasion and migration via the HIF-1α/MCT4/MCT1 signaling pathway. These findings reveal that PDGFR-β/Cav-1-mediated autophagy in CAFs enhances breast cancer cell invasion, migration, and epithelial-mesenchymal transition (EMT), collectively highlighting the crucial role of CAFs autophagy in facilitating breast cancer progression. The study elucidates the mechanism by which PDGFR-β/Cav-1 promotes breast cancer progression through autophagy regulation in CAFs, These findings provide a theoretical basis for potential therapeutic method for treating breast cancer.